(3GdfGaY aj eNJUQ GdTQGFYs - (3GdgPdj, GdMdj, CHh GdbGSe, fLe GdOjf, GdeMbb GdMdj, LYaQ Hf GdMSf Hf jMji Hf GdMSjf, J(B676(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj UZQJ aj aj YXeJg YHGOGJ GdYGHOjf(B... (3CeG HYO aEfj ehQOc aj gPG GdeNJUQ NdGUI GdePgH GdeYJHQ HCdaGX eMHQI hYHGQI eMQQI(B...s
(3BNQgG (B:s
(3dG jYbd GdYGbdI YeOG hdG CaQGOG (B... (3hjNJU VeGfgG (B... (3Ydi GdBOej MSH agPG BNQ eG CQOfG PcQg hbUOfG MUQgs
(3JHUQI GdYfhGf (B:s
(3GdeNJUQ GdfGaYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI HQbe(B: 2636s
(3GdPQjYI HQbe(B: 2636s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis